HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN STATUS GIZI BAYI PADA BAYI USIA 4 - 6 BULAN - ELVIZA LISMI ADYANI; HEPPY JELITA SARI (JURNAL ILMIAH KOHESI, 2020)
Exclusive breastfeeding is breast milk given to babies from birth for 6 months, without adding and/or replacing with other foods or drinks. The implementation of Exclusive Breastfeeding has several benefits, one of which is to reduce infant mortality. However, the prevalence of the implementation of Exclusive ASI in Indonesia is still very low. The purpose of the study was to find out whether or not there is a relationship between exclusive breastfeeding on the nutritional status of infants, especially in infants aged 4 - 6 months. This type of research was descriptive analytic research with a cross - sectional design. The subjects in this study were infants aged 4 - 6 months at Melati Pasar VI Puskesmas Melati II Village, Perbaungan District, North Sumatra in November 2018, with total of 24 people. This research uses total sampling and data analysis using the Fisher test. Data retrieved through filling in questionnaires, weighing body weight, measuring height, upper arm circumference and head circumference. The study results of infants that exclusively breastfed with good nutritional status as many as 15 people (88.2%), infants who were given exclusive breastfeeding with poor nutritional status as many as 2 people (11.8%), infants who were not breastfed exclusively comes up with good nutritional status by 1 person (14.3%) and babies that are not given exclusive breastfeeding with poor nutritional status as many as 6 people (85.7%). Fisher's test results obtained p - value = 0.001. There is a relationship between exclusive breastfeeding on the nutritional status of infants, especially in infants aged 4 - 6 months.